Le ultramaratone: un altro genere di competizione - Dominici, Greta; Dragotto, Francesca (Eracle. Journal of Sport and Social Sciences, 2020)
The contribution aims to describe that increasingly important sport phenomenon known as ultramarathon. An ultramarathon is usually described as a competitive race, mainly a footrace, which lasts much longer than any other ordinary marathon. The authors have taken into consideration its many aspects and have embedded them into a historical (also from a linguistic perspective) and sociocultural framework. In the first part of the paper, the authors focus on the nature and the elements that constitute an ultra-marathon, the actors involved and the percentage of female athletes. In the second part, in order to examine the relationship between the extension of the phenomenon and its social representation, they introduce and analyze a corpus collected from the Italian press, both mainstream and non-mainstream. The data-set is made of articles published between 2018 and April 2020: in all the text taken into consideration, the authors have provided with a qualitative analysis finalized to highlight – among other elements - the presence of gender-markedness clues.